2019
DOI: 10.1177/1550059419872414
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in QEEG in Psychopath Offenders

Abstract: Introduction. Functional brain differences related to sex in psychopathic behavior represent an important field of neuroscience research; there are few studies on this area, mainly in offender samples. Objective. The aim of this study was to investigate the presence of electrophysiological differences between male and female psychopath offenders; specifically, we wanted to assess whether the results in quantitative EEG, low-resolution electromagnetic tomography (LORETA), and changes in synchronous brain activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Several studies have indicated that antisocial behavior, especially aggression and impulsivity, are associated with dysfunctions in the prefrontal cortex [8][9][10][11][12][13][14]. Following the proposed neurocognitive models of Blair [15][16][17], violence is inhibited by empathy, stating that individuals with deficits in their empathic abilities could be less susceptible and less motivated to inhibit aggression, which proliferates the risk of violent behavior.…”
mentioning
confidence: 99%
“…Several studies have indicated that antisocial behavior, especially aggression and impulsivity, are associated with dysfunctions in the prefrontal cortex [8][9][10][11][12][13][14]. Following the proposed neurocognitive models of Blair [15][16][17], violence is inhibited by empathy, stating that individuals with deficits in their empathic abilities could be less susceptible and less motivated to inhibit aggression, which proliferates the risk of violent behavior.…”
mentioning
confidence: 99%
“…Both studies confirm that adult males convicted of violent crimes had gray matter reductions in the prefrontal cortex and temporal gyrus, areas consistently implicated in emotional control, antisocial behavior, and reactive aggression. Two other studies also utilized the same method: EEG ( Keune et al, 2017 ; Calzada-Reyes et al, 2020 ). However, Keune et al (2017) focused on alpha wave asymmetry to probe approach vs. withdrawal behavior, while Calzada-Reyes et al (2020) focused on beta activity to analyze differences between psychopathic females and males in terms of excitability or arousal.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies also utilized the same method: EEG ( Keune et al, 2017 ; Calzada-Reyes et al, 2020 ). However, Keune et al (2017) focused on alpha wave asymmetry to probe approach vs. withdrawal behavior, while Calzada-Reyes et al (2020) focused on beta activity to analyze differences between psychopathic females and males in terms of excitability or arousal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations